Data Structures and Algorithms Using C++. - Akepogu, Ananda Rao.; Palagiri, Radhika Raju. (1900)
Data Structures and Algorithms Using C++ helps students to master data structures, their algorithms and the analysis of complexities of these algorithms. Each chapter includes an Abstract Data Type (ADT) and applications along with a detailed explanation of the topics. This book meets the requirements of the course curricula of all Indian universities.
13.3.3 Deletion -- 13.3.4 Drawbacks of m-Way Search Trees -- 13.4 B Trees -- 13.5 Operations on B Trees -- 13.5.1 Searching -- 13.5.2 Insertion -- 13.5.3 Deletion -- 13.6 Height of B Trees -- 13.7 Variations of B Tree -- 13.7.1 B* Tree -- 13.7.2 B+ Tree -- 13.8 Applications -- 13.8.1 Databases -- Summary -- Exercises -- Chapter 14 Red-Black Trees and Splay Trees -- 14.1 Introduction -- 14.2 Representation of a Red-Black Tree -- 14.3 Operations -- 14.3.1 Searching -- 14.3.2 Insertion -- 14.3.3 Deletion -- 14.4 Splay Trees -- 14.4.1 Splay Rotations -- 14.4.2 Amortized Analysis -- 14.5 Applications -- Summary -- Exercises -- Chapter 15 Pattern Matching and Tries -- 15.1 Introduction -- 15.2 Terminology -- 15.3 Pattern Matching Algorithms -- 15.3.1 Fixed Pattern Matching Algorithms -- 15.3.2 Regular Expression Pattern Matching -- 15.4 Fixed Pattern Matching Algorithms -- 15.4.1 Brute Force Pattern Matching Algorithm -- 15.4.2 Th e Boyer-Moore Algorithm -- 15.4.3 Knuth-Morris-Pratt Algorithm (KMP) -- 15.5 Applications of Pattern Matching Algorithms -- 15.6 Tries -- 15.6.1 Standard Tries -- 15.6.2 Compressed Tries -- 15.6.3 Suffix Tries -- 15.7 Applications of Tries -- Summary -- Exercises -- Chapter 16 Sorting and Searching -- 16.1 Sorting -- 16.1.1 Bubble Sort -- 16.1.2 Insertion Sort -- 16.1.3 Selection Sort -- 16.1.4 Quick Sort -- 16.1.5 Merge Sort -- 16.1.6 Shell Sort -- 16.1.7 Radix Sort -- 16.1.8 Heap Sort -- 16.2 Searching -- 16.2.1 Linear Search or Sequential Search -- 16.2.2 Binary Search -- 16.2.3 Fibonacci Search -- Summary -- Exercises -- Index.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books